Relationship between the general condition of acute lymphoblastic leukemia patients with remission rate and convulsion as an adverse effect chemotherapy - Rusdi Andid; Nurdiani Nurdiani; Bidasari Lubis; Adi Sutjipto (Indonesian Pediatric Society, 2001)
A retrospective study on the relationship between the general condition of acute lymphoblastic leukemia patients with remission rale and convulsion as an adverse effect of chemotherapy was conducted in leukemia patients of the hematology-oncology subdivision, Departmenl of Child Health, Medical School, University of North Sumatra, Medan. Of 114 children with acute lymphoblastic leukemia, 81 (71.05%) received chemotherapy, 31 patients among them was in good general condition. Remission rate of the 31 patients was 80.6% (25 children). Whereas in the remaining 50 patients, the remission rate among them was 84% (42 patients). There was no significant relationship between their general condition to the recurrence rate of acute lymphoblastic leukemia patients who had been administered chemotherapy during induction phase. Convulsion was found In 2 cases, due to CNS leukemia.